2019
DOI: 10.37358/rc.19.6.7301
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Thrombosis and Gut Microbiota: Understanding the Burden

Abstract: Portal vein thrombosis (PVT) continues to be challenging, due to its versatile features and associated clinical pitfalls. This study aimed to explore whether gut microbiota imbalance (GMI) could alter clinical presentation and short term outcome in cirrhotic patients with PVT. We conducted a cross-sectional exploratory study, concerning 50 consecutive cirrhotic patients with PVT recruited during hospitalization. Consecutive to stool microbiological exams, they were assigned into two groups: 25 GMI positive as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Ferahman et al supported this trend, with ICU admissions increasing to 37.03% during the pandemic, up from 32.3% in the pre-pandemic period [35]. Studies have reported significant increases in postoperative complications, including intestinal fistulas, during the pandemic [18,20,56,57].…”
Section: Discussionmentioning
confidence: 92%
“…Ferahman et al supported this trend, with ICU admissions increasing to 37.03% during the pandemic, up from 32.3% in the pre-pandemic period [35]. Studies have reported significant increases in postoperative complications, including intestinal fistulas, during the pandemic [18,20,56,57].…”
Section: Discussionmentioning
confidence: 92%
“…Over the past decades, many studies have emphasized the association between dysbiosis and various digestive conditions, either functional or organic [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. GSD is one of many digestive diseases that are frequently associated with gut microbiota dysbiosis, either in humans or in experimental animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbes can also synthesize substances that affect platelets through serotonin and may enhance von Willebrand factor production [ 47 ]. A study of elderly patients found that patients with probiotic deficiency in the gut exhibited higher inflammatory status, hypoalbuminemia, and severe portal vein thrombosis (PVT) [ 48 ]. These studies showed that gut microbes were closely related to thrombosis, and interventions in gut microbiota might play a key role in thrombosis.…”
Section: Discussionmentioning
confidence: 99%